52-Year-Old Male with Mature Cataract, Class II Obesity, and Grade II Hypertension with Genetic and Personal Behavior Risk Factors - Dwi Rahayu, Indriati; Atha Erhansyah, Sadam (Jurnal Ilmu Kedokteran Keluarga, 2026)
Background: The co-occurrence of cataract, obesity, and hypertension represents a complex challengein primary care, requiring a holistic management approach. This case examines a patient with theseinterrelated conditions and significant behavioral risk factors. Objective: To describe thecomprehensive management of a patient with mature cataract, Class II Obesity, and Grade 2Hypertension using a family medicine approach. Case: A 52-year-old male presented with progressivevision loss in his right eye over two years. Examination revealed mature cataract (OD vision 3/60),obesity (BMI 33.46 kg/m2), and hypertension (BP 164/94 mmHg). Risk factors included smoking,unhealthy diet, physical inactivity, and family history of hypertension. Management: Interventionsincluded surgical referral for cataract, dual antihypertensive therapy (amlodipine and lisinopril), andlifestyle modification for obesity. Family assessment revealed high functionality (APGAR score 10).Results: Cataract surgery improved visual acuity to 6/24. However, hypertension remaineduncontrolled (176/116 mmHg) at follow-up, while obesity management showed limited progress. Thefamily provided strong support throughout care. Conclusion: While targeted specialist interventionsuccessfully addressed the cataract, the persistence of uncontrolled hypertension and obesityunderscores the need for sustained, integrated management of multiple chronic conditions in primarycare, emphasizing continuous lifestyle modification and medication adherence.